Digital Transformation Strategy of SMEs Development in Framework for Todays (Case Study on Borondong Industry) - Miharja, Rediawan; Muhammad, Rabhi Fathan (Banking & Management Review, 2022)
This research aims to find out the implementation of strategies that can be carried out by SMEs in order to build a framework for era 4.0. This research presents the concept of a technology transformation development strategy for SMEs. The method in this research is utilized a qualitative approach, using SWOT tools combined with the Business Model Canvas for SMEs. The results of this study identified development factors in the framework of the company's strategy to face era 4.0, especially for SMEs in the Borondong Industry case study. The main finding of this research is that SMEs need to carry out specific strategies related to the proper technology adoptions in stages. The implications of the theory that can be implemented in this research are conceptual strategies that may contribute significantly to the SMEs.